2011
DOI: 10.1039/c0gc00513d
|View full text |Cite
|
Sign up to set email alerts
|

Platinum nanoparticles using wood nanomaterials: eco-friendly synthesis, shape control and catalytic activity for p-nitrophenol reduction

Abstract: We report a one-step and environment-friendly synthesis of platinum nanoparticles with controlled shapes and sizes using wood nanomaterials in aqueous phase without employing any other reductants, capping or dispersing agents. This green process affords an easy route to the production of shape-selective metal nanoparticles. The obtained spherical and cubic Pt nanoparticles and spherical Pt nanoclusters exhibit high activities in the catalytic reduction of pnitrophenol as a model reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(91 citation statements)
references
References 36 publications
2
89
0
Order By: Relevance
“…The electron-rich feature of hydroxyl and sulfate ester groups on its surface endow CNs a good colloidal stability in water, which makes it well suitable for the preparation of metal NPs (Benaissi, Johnson, Walsh, & Thielemans, 2010;Hirai, Nakao, & Toshima, 1979;Lin et al, 2011). However, to date, the use of CNs in the biosynthesis of metal NPs is very limited.…”
Section: Introductionmentioning
confidence: 98%
“…The electron-rich feature of hydroxyl and sulfate ester groups on its surface endow CNs a good colloidal stability in water, which makes it well suitable for the preparation of metal NPs (Benaissi, Johnson, Walsh, & Thielemans, 2010;Hirai, Nakao, & Toshima, 1979;Lin et al, 2011). However, to date, the use of CNs in the biosynthesis of metal NPs is very limited.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the low stability of these colloidal nanoparticles against agglomeration diminishes their reusability performances, which is one of the most important criterias in the heterogeneous catalysis. In this context, the generation of the metal nanoparticles on solid support materials has already been acknowledged for preventing aggregation of active metal nanoparticles and providing high reusability performances in the nitrophenols reduction [37][38][39][40]. Additionally, the use of supported metal nanoparticles as nanocatalyst in the reduction of nitrophenols may provide a kinetic control of the catalytic reaction, whereas it is almost impossible in the catalytic employment of colloidal metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of platinum nanoparticles using Diopyros kaki leaf extract was reported by (Song et al, 2010) in which he has shown the dependency of size on the reaction temperature and the concentrations of leaf broth and PtCl 6 2-. In another effort, wood nanomaterials in aqueous phase was used to synthesize platinum nanoparticles with controlled shapes and sizes (Lin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%